Riding with flow : menstrual health in World Cup and World Championship mountain bikers : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Exercise and Sport Science at Massey University, Wellington, New Zealand - Moller, Mary-Ann Rongo (Massey University, 2022)
Background: Menstrual health is an indicator of overall health and is an important aspect of female athlete physiology. Menstrual disturbances can have long term health consequences and are most likely related to high training volumes, disordered eating, and low energy availability. While menstrual health has been studied in some sports, it has been neglected in mountain biking. Objective: To report the menstrual health status of female World Cup and World Championship Mountain bikers with a specific focus on 1) the prevalence of menstrual disturbances; 2) hormonal contraceptive use; and 3) menstrual cycle symptomology and period characteristics. A secondary aim of this research was to compare the menstrual health of cross-country riders and downhill riders. Methods: An online survey was made available for female mountain bikers competing in the 2021 season of the UCI Mountain Bike World Cup Series, World Championships and Tokyo Olympics. There were a total of 76 valid survey responses. Results: Riders were 85.5% (n = 65) cross-country riders and 14.5% downhill riders (n = 11). The prevalence of menstrual disturbances was 58% (n = 44), with 34% of riders reporting amenorrhea (n = 26) and 47% oligomenorrhea (n = 36). There were no significant age or discipline differences in menstrual disturbances. Twenty-five percent of riders (n = 19) were current hormonal contraceptive users. About a third of riders (29%, n = 22) experienced heavy menstrual bleeding. Fifteen percent of riders (n = 11) had been diagnosed with eating disorders, 58% (n = 44) engaged in disordered eating practices and 9% (n = 7) had been diagnosed with Relative Energy Deficiency in Sport (RED-S ). Conclusions: Over half of all riders in this study had experienced menstrual disturbances. Negative menstrual cycle symptoms were experienced by most. There were no significant differences in menstrual health when comparing cross-country and downhill riders. Eating disorders and associated behaviours were relatively high in mountain bikers and in the higher level riders this was only seen in cross-country riders. Male coaches were a barrier to communication around the menstrual cycle for some female athletes.
Keywords: 420702 Exercise physiology